Los mitos de la escuela - Pumares Puertas, Luis (Revista Complutense de Educación, 2006)
Although everyone might easily agree that teaching is the most important role among those that can be assigned to schools, or so it seems, at least, from the point of view of educators that is, yet there are some elements, to which teachers refer when they argue that such educative task, beyond mere training, finds itself handicapped and, at times, impaired: I have called those elements myths. "The myths of school". On the following pages I have tried both to identify and describe some of them with the sole idea of "demystifying them" and pulling them out of the privacy of the teaching discourse and prove that they are nothing but shields, behind which we protect ourselves from the stress and loneliness felt by many teachers whilst carrying out their tasks, and, sometimes, somehow, prevent us from finding the right path.